DIFFUSION BONDING AND POST-BOND HEAT TREATMENT OF SIALON TO NITRIDED A lSI 420 STAINLESS STEEL - MD. IBRAHIM, NOR NURULHUDA (2015)
Sialon and stainless steel are two different classes of materials which have their own uniqueness. Joining these materials will produce an effective component design by benefitting the high strength of the steel in supporting the sialon at high service temperature. Therefore, this research had been conducted to investigate the potentiality in joining sialon to AlSl 420 stainless steel. Prior to diffusion bonding of these materials, the steel was nitrided at 1200°( for one and four hours. The bonding process was performed at 1200QC under a uniaxial pressure of 17 MPa in a vacuum for one, two, and three hours. Increasing the bonding time produced thicker reaction layer The thinnest layer was formed in joining sial on to four hour nitrided steel. From EDX, XRD, and Raman analysis, no indication pointed to the presence of FeSi in the joint of sialon-nitrided steels. There was no crack observed in all diffusion bonded samples However, the diffusion layer and the steel were segregated.